2005
DOI: 10.1111/j.1439-0442.2005.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Fibre Intake in a Group of Captive Giraffe (Giraffa camelopardalis) Offered Increasing Amounts of Browse

Abstract: We investigated the effect of diet on intake of energy and fibre in a group of three captive adult giraffe by weighing offered diet items and leftovers for 7 days after an adaptation period of 7 days. Digestion coefficients were calculated using, as internal marker, the acid detergent lignin content of a faecal sample pooled from subsamples taken during the last 5 days of intake measurement. Two lucerne hay-only diets of differing quality (L1, L2) were fed, as well as the regular diet of lucerne hay and concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 8 publications
(24 reference statements)
2
29
1
Order By: Relevance
“…In contrast, the addition of 6 kg of the same browse material did not increase the overall intake any further. 37 However, the browse was always consumed completely, and total DM intake is only one parameter of interest; in particular, long-term effects of such a feeding regimen are difficult to document.…”
Section: Ration Compositionmentioning
confidence: 99%
“…In contrast, the addition of 6 kg of the same browse material did not increase the overall intake any further. 37 However, the browse was always consumed completely, and total DM intake is only one parameter of interest; in particular, long-term effects of such a feeding regimen are difficult to document.…”
Section: Ration Compositionmentioning
confidence: 99%
“…It has been observed that giraffe do not ingest grass hay or alfalfa hay, if fed this food alone, in quantities that one would expect for a ruminant of this size. 15,24 A potential inadequacy of hays offered has been suspected to be a major contributing cause to the difficulties experienced in giraffe feeding. 7 One of the major health issues in captive giraffe is the phenomenon of animals dying of unknown causes, often having serous fat atrophy at necropsy (formerly termed ''peracute mortality syndrome'').…”
Section: Introductionmentioning
confidence: 99%
“…Many northern zoos house giraffe in two separate spaces depending on season, although little information is available regarding whether they experience behavioral variation between these two seasonal exhibits. Similarly to cattle, giraffe behavior consists of high foraging levels (Duggan, Burn, & Clauss, 2015;Hatt et al, 2005). Wild populations of giraffe are reported to spend about 60% of the daytime foraging (Bashaw, Tarou, Maki, & Maple, 2001;Pellew, 1984).…”
mentioning
confidence: 99%